Probiotic-Green Tea Yoghurt on Improving Testicular Histology of High-fat and Fructose Diet Mice - Izati, Rahmi; Al Faizah, Belinda Nabiila; Fadlilah, Dawama Nur; Kavitarna, Septhyanti Aprilia; Sa'adah, Nur Alfi Maghfirotus; Ardiansyah, Esha; Atho'illah, Mochammad Fitri; Arifah, Siti Nur; Rifa'i, Muhaimin; Jatmiko, Yoga Dwi; Rahayu, Sri (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
An unhealthy lifestyle can cause changes in the body's metabolism, leading to obesity. The development of obesity is supported by a disturbance in gut microbiota balance that triggers visceral fat deposition in organs such as the testes. Excess fat deposition triggers inflammation, dysfunction, and high ROS production that can damage testicular tissue. Yoghurt, a fermented milk product fortified with green tea, is high in antioxidants that can help reduce excess ROS. Adding encapsulated probiotics in yoghurt can stabilize the gut microbiota in obesity so that dysbiosis can be resolved. This study was conducted to determine the potential of green tea-probiotic yoghurt (GTY) on testicular tissue repair in mice fed a high-fat and fructose diet (HFFD). The research procedure includes feeding HFFD for 3 months, calculating the Lee index, lactic acid bacteria preparation, microencapsulated probiotics, yoghurt preparation, treatment, data collection, including relative weight of testes, the diameter of seminiferous tubules (DST), the epithelium thickness (ET), the number of Leydig cells (LC), and the number of spermatogenic cells. The mice groups were divided into normal (P0), HFFD (P1), HFFD + simvastatin 1.3 mg/Kg BW (P2), HFFD + plain yoghurt 5 g/Kg BW (P3), HFFD + GTY 2.5 g/Kg BW (P4), HFFD + GTY 5 g/Kg BW (P5), and HFFD + GTY 10 g/Kg BW (P6). The results showed that green tea infusion yoghurt with encapsulated probiotics could improve the structure of testicular tissue in mice after HFFD administration. The most effective dose is green tea yoghurt 5 g/Kg BW.